Impact of systemic Immune-inflammation Index on oncologic outcomes in patients treated with radical prostatectomy for clinically nonmetastatic prostate cancer - Rajwa, Pawel; Schuettfort, Victor M; D'Andrea, David; Quhal, Fahad; Mori, Keiichiro; Katayama, Satoshi; Laukhtina, Ekaterina; Pradere, Benjamin; Motlagh, Reza Sari; Mostafaei, Hadi; Grossmann, Nico C; Huebner, Nicolai; et al. (Urologic oncology, 2021)
PURPOSE: To evaluate the predictive and prognostic value of the Systemic Immune-inflammation Index (SII) in a large cohort of patients treated with radical prostatectomy (RP) for clinically non-metastatic prostate cancer (PCa). METHODS: We retrospectively analyzed our multicenter database comprising 6,039 consecutive patients. The optimal preoperative SII cut-off value was assessed with the Youden index calculated on a time-dependent receiver operating characteristic (ROC) curve. Logistic regression and Cox regression analyses were used to investigate the association of SII with pathologic features and biochemical recurrence (BCR), respectively. The discriminatory ability of the models was evaluated by calculating the concordance-indices (C-Index). The clinical benefit of the implementation of SII in clinical decision making was assessed using decision curve analysis (DCA). RESULTS: Patients with high preoperative SII (≥ 620) were more likely to have adverse clinicopathologic features. On multivariable logistic regression analysis, high preoperative SII was independently associated with extracapsular extension (odds ratio [OR] 1.16, P = 0.041), non-organ confined disease (OR 1.18, P = 0.022), and upgrading at RP (OR 1.23, P < 0.001). We built two Cox regression models including preoperative and postoperative variables. In the preoperative multivariable model, high preoperative SII was associated with BCR (hazard ratio [HR] 1.34, 95% CI 1.15-1.55, P < 0.001). In the postoperative multivariable model, SII was not associated with BCR (P = 0.078). The addition of SII to established models did not improve their discriminatory ability nor did it increase the clinical net benefit on DCA. CONCLUSION: In men treated with RP for clinically nonmetastatic PCa, high preoperative SII was statistically associated with an increased risk of adverse pathologic features at RP as well as BCR. However, it did not improve the predictive accuracy and clinical value beyond that obtained by current predictive and prognostic models. SII together with a panel of complementary biomarkers is praised to help guide decision-making in clinically nonmetastatic PCa.
Keywords: Prostatic Neoplasms; Radical prostatectomy; nádory prostaty; Humans; Prostate cancer; lidé středního věku; Aged; Inflammation; výsledek terapie; senioři; lidé; Biomarkers; zánět; Prostatectomy; BCR; Male; Middle Aged; Retrospective Studies; SII; prognóza; Treatment Outcome; retrospektivní studie; prostatektomie; mužské pohlaví; Prognosis